MicroRNA-503-5p protects streptozotocin-induced erectile dysfunction in diabetic rats by downregulating SYDE2: MicroRNA-503-5p protects ED by SYDE2 - Li, Gangqin; Jiang, Lin; Bai, Kuan; Tan, Guangxing (Cellular and Molecular Biology, 2024)
Plentiful studies have clarified miRNAs take on a key role in the sexual dysfunction of diabetic rats. This study aimed to figure out microRNA (miR)-503-5p/SYDE2 axis’ latent mechanisms in streptozotocin-induced diabetic rat sexual dysfunction. A model of erectile dysfunction (ED) in diabetic rats was established by injecting streptozotocin. MiR-503-5p and SYDE2 in ED rats were altered by injection of miR-503-5p mimic or si/oe-SYDE2. The targeting link between miR-503-5p and SYDE2 was testified. ICP/MAP value was tested by pressure sensor; Penile capillary abundance was assessed; Penile cGMP and AGEs were detected; penile smooth muscle cell apoptosis was assessed; MiR-503-5p and SYDE2 were tested. In streptozotocin-induced ED rats, miR-503-5p was reduced and SYDE2 was elevated. Elevating miR-503-5p or silencing of SYDE2 can enhance penile erection rate, ICP/MAP value, capillary abundance, and cGMP but reduce AGEs and penile smooth muscle cell apoptosis rate in ED rats. Strengthening SYDE2 with elevating miR-503-5p turned around the accelerating effect of elevated miR-503-5p on penile erection in ED rats. SYDE2 was a downstream target gene of miR-503-5p. MiR-503-5p protects streptozotocin-induced sexual dysfunction in diabetic rats by targeting SYDE2.